Florida Solid and Hazardous Waste Regulation Handbook: Hazardous Materials Transportation Authorization Act (HMTAA) - Michael T. Olexa; Aaron Leviten; Kelly Samek (EDIS, 2004)
In 1994, Congress enacted the Hazardous Materials Transportation Authorization Act (HMTAA) to provide protection against the risks to life and property during the transportation of hazardous materials. HMTAA broadened the regulatory and enforcement authority of the Secretary of Transportation. The statute is so comprehensive that it covers the transportation of hazardous materials by: aircraft, rail, ships, and vehicles. This is EDIS document FE449, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, UF/IFAS, University of Florida, Gainesville, FL. Published December 2003.